A NEW METHOD FOR DETERMINING PARAMETERS OF PHOTOVOLTAIC MODULE BASED ON THE DATA FROM TECHNICAL SPECIFICATION - Obukhov, S.G.; Plotnikov, I.A.; Klimova, G.N. (KU Publ., 2022)
In the given article the methodology of making a photovoltaic module mathematical model is presented, which lets reproduce its energy characteristics in real operating conditions. Also, the major types of mathematical models of photovoltaic converters are discussed and most well-known estimation methods of their parameters are analyzed. An original and simple way of parameters definition of photovoltaic module is introduced based on the technical specification data without using programming and developing numerical estimation algorithms. The suggested method is easily realized in the tabular program Excel with installed tool «Search for solutions». The simulation results of volt-ampere characteristic (V-I curve) of photovoltaic module Kyocera KC200GT are presented in a wide variation range of temperature and illumination. In addition, an accuracy evaluation is made by comparing the model characteristics and experimental data. The model was tested on a number of photovoltaic modules and proved good modeling results compliance with manufacturer’s data. The model provides a high modeling accuracy around MPP (maximum power point). This fact allows to use it for development of effective algorithms for photovoltaic power stations controllers, circuit design advancement of converting devices, prediction of power generation, operating modes analysis and optimization for photovoltaic systems.
Keywords: photovoltaic module; solar cells; single diode model; parameters extraction photovoltaic panel